Acute Decrease of Cerebral Oxygen Saturation during Rapid Ventricular and Supraventricular Rhythm: A Pilot Study. Issue 9 (16th May 2014) - WUTZLER, ALEXANDER; OTTO, NATALIE; GRÄSER, SASKIA; BOLDT, LEIF‐HENDRIK; HUEMER, MARTIN; PARWANI, ABDUL; HAVERKAMP, WILHELM; STORM, CHRISTIAN
<x xml:space="preserve">Abstract</x> Background Monitoring of cerebral tissue oxygen saturation (SctO2) reflects cerebral microcirculation. We sought to characterize the decrease in SctO2 during supraventricular tachycardia (SVT) and ventricular tachycardia (VT) in adults. Methods Twenty patients (mean age: 46.3 ± 18.1 years, 40% men) were included. Rapid atrial and ventricular pacing (200/min) was used as a model for VT and SVT. Near‐infrared spectroscopy (NIRS) was used to measure SctO2. Results Atrial stimulation decreased right (P = 0.014) and left (P = 0.019) hemispheric SctO2 compared to baseline. Ventricular stimulation also decreased right (P < 0.001) and left (P < 0.001) hemispheric SctO2. A negative correlation between age and minimal value under stimulation was found for atrial (right SctO2 r = –0.641, P = 0.034; left SctO2 r = –0.694, P = 0.018) and ventricular pacing (right SctO2 r = –0.564, P = 0.01; left SctO2 r = –0.604, P = 0.005). A positive correlation was found between left ventricular ejection fraction (LVEF) and minimal value under ventricular stimulation (right SctO2 r = 0.567, P = 0.009; left SctO2 r = 0.471, P = 0.036). Conclusion Cerebral perfusion decreased during simulated SVT and VT and is influenced by age and LVEF. Clinicians can consider NIRS monitoring in patients during ablation procedures and in critical care. NIRS may especially be appropriate for the elderly and for patients with impaired LVEF.